The Power of Husband-Wife Communication in Building Family Resilience and Preventing Divorce: A Study of Maṣlaḥah Mursalah - Teguh Mulyo, Mufrod; Nasution, Khoiruddin; Batubara, Samin; Musawwamah, Siti; Abdullah, Raihanah (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
This paper is prepared based on the research on 18 couples of husbands and wives from a faculty at a state Islamic university in Yogyakarta. The research found that good communication between husbands and wives in household life could build family resilience and prevent divorce. This study used normative-sociology approach combined with the maṣlaḥah mursalah and convergence theories, which was further combined with the Ibnu Miskawaih and K. Hajar Dewantoro’s theories. The data was collected by distributing questionnaires to 18 couples of husbands and wives. The study found that a good communication between wives and husbands could be built through verbal and non-verbal communications. These verbal and non-verbal communications had the same strength in building a good communication, depending on the situations. There were times when it was more appropriate to use verbal communication, while there were also times when non-verbal communication was the right choice. It could, therefore, be said that communication played a crucial role in building family resilience. Thus, analyzed using the maṣlaḥah mursalah theory, it was not an exaggeration to state that building communication is a necessity for husbands and wives. It is not even exaggerating to say that building a good communication is an obligation that husbands and wives cannot ignore.